2015
DOI: 10.2139/ssrn.2633944
|View full text |Cite
|
Sign up to set email alerts
|

Intertemporal Pro-Poorness

Abstract: A long-lasting scientific and policy debate queries the impact of growth on distribution. A specific branch of the micro-oriented literature, known as 'pro-poor growth', seeks in particular to understand the impact of growth on poverty. Much of that literature supposes that the distributional impact should be measured in an anonymous fashion. The income dynamics and mobility impacts of growth are thus ignored. The paper extends this framework in two important manners. First, the paper uses an 'intertemporal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The year 2000 marks the transition from the autocratic rule of Suharto, the recovery from the Asian financial crisis, the beginning of a process of decentralization, and, subsequently, the commodity boom -four different economic, political, and social events that arguably had an impact on people's lives and so on their income trajectories. Several studies (e.g., Bresson et al 2017;Grimm 2007;Lo Bue and Palmisano 2020), including the present one, have shown that there has been growth in this period and that the incidence of growth has been larger among the initially poor. But why do the poor exhibit higher growth rates than those individuals initially belonging to richer percentiles?…”
Section: Discussionsupporting
confidence: 51%
“…The year 2000 marks the transition from the autocratic rule of Suharto, the recovery from the Asian financial crisis, the beginning of a process of decentralization, and, subsequently, the commodity boom -four different economic, political, and social events that arguably had an impact on people's lives and so on their income trajectories. Several studies (e.g., Bresson et al 2017;Grimm 2007;Lo Bue and Palmisano 2020), including the present one, have shown that there has been growth in this period and that the incidence of growth has been larger among the initially poor. But why do the poor exhibit higher growth rates than those individuals initially belonging to richer percentiles?…”
Section: Discussionsupporting
confidence: 51%
“…Second, the framework proposed in this paper could be extended to endorse an intertemporal perspective, as recently explored in Bresson et al . (), which does not simply compare in a non‐anonymous fashion the initial and the final periods, but is able to account for the income and status variation of individuals between these two periods. These extensions will be the subject of future research.…”
Section: Discussionmentioning
confidence: 99%
“…the class of SEFs constructed as in(4) and with social weight functions satisfying Properties 1.Ŵ 1,2 is the class of SEFs constructed as in (4) and with social weight functions satisfying Properties 1 and 2.Ŵ 1,3 is the class of SEFs constructed as in (4) and with social weight functions satisfying Properties 1 and 3. Ŵ 1,4 is the class of SEFs constructed as in (4) and with social weight functions satisfying Properties 1 and 4.…”
mentioning
confidence: 99%